Hospital water and prevention of waterborne infections. Issue 1 (January 2016) - Spagnolo, Anna Maria; Orlando, Paolo; Perdelli, Fernanda; Cristina, Maria Luisa
Abstract : The hospital water system may constitute a reservoir for microorganisms, such as Pseudomonas aeruginosa, Burkholderia cepacia, Stenotrophomonas maltophilia, Legionella pneumophila, Acinetobacter spp., mycetes, non-tubercular mycobacteria, and so on, which can cause healthcare-associated infections. Indeed, it has been revealed that 20–50% of cases of nosocomial colonization/infection due to P. aeruginosa are sustained by waterborne strains. Waterborne infections can be spread not only through the ingestion of contaminated water but also by contact with or the inhalation of aerosols. Immunocompromised patients are particularly susceptible to infection by such microorganisms, many of which are multi-resistant to antibiotics. Healthcare effects range from colonization of the airways and urinary tracts to bacteraemia and disseminated infections. In 2011, the WHO issued guidelines on the quality of water for human consumption, including hospital water supplies. In risk assessment and management, these guidelines adopt criteria centred on preventive measures rather than remedial action alone. The guidelines recommend the adoption of a Water Safety Plan for water-risk management. By providing safe water, proper implementation of the Water Safety Plan ensures patient safety and reduces costs, in that waterborne infections prolong hospitalisation and increase morbidity, mortality, treatment costs and compensation claims.